2020
DOI: 10.1101/2020.10.20.347864
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Auditory Decisions in the Supplementary Motor Area

Abstract: In human speech and communication across various species, recognizing sounds is fundamental for the selection of appropriate behaviors. But how does the brain decide which action to perform based on sounds? We explored whether the premotor supplementary motor area (SMA), responsible for linking sensory information to motor programs, also accounts for auditory-driven decision making. To this end, we trained two rhesus monkeys to discriminate between numerous naturalistic sounds and words learned as target (T) o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…21 Also, as a premotor cortex, the SMA participates in voluntary movement control, [22][23][24] working memory, and decision making. [25][26][27][28] In humans, it is also involved in acoustic imagery. 20 Recently, Vergara and collaborators showed that the SMA is crucial for auditory decisions 1 .…”
Section: Introductionmentioning
confidence: 99%
“…21 Also, as a premotor cortex, the SMA participates in voluntary movement control, [22][23][24] working memory, and decision making. [25][26][27][28] In humans, it is also involved in acoustic imagery. 20 Recently, Vergara and collaborators showed that the SMA is crucial for auditory decisions 1 .…”
Section: Introductionmentioning
confidence: 99%